Thyroid follicular carcinoma-like renal tumor: A case report and literature review. Issue 21 (May 2018) - Zhang, Yujie; Yang, Jing; Zhang, Mingfang; Meng, Zhaowei; Song, Wenjing; Yang, Long; Li, Liming; Wang, Dan; Shi, Tao
Abstract: Rationale: Thyroid follicular carcinoma-like renal tumor (TFCLRT) is a rare primary renal epithelial tumor that was first reported in 2006. We report a case diagnosed of TFCLRT by us to observe the pathological feature and analyze comparatively the clinical and pathologic characteristics with all cases of reviewed literatures. Patient concerns: A 54-year-old female patient had the urinary frequency with the symptom of right flank pain with a history of more than half a year of hypertension and received uterine fibroid resection 12 years ago. B-mode ultrasound examination and renal magnetic resonance showed a right renal sinus nodule. Diagnoses: Histopathology revealed thyroid follicle-like structures of different sizes, containing a colloid-like substance, while the periodic acid-Schiff (PAS) and diastase-resistant PAS staining confirmed that it was mucus protein. Immunohistochemical staining showed that it expresses the transcription factor PAX-8 but does not express the thyroid-specific antibodies TG and TTF-1. Interventions: The patient underwent a tumor enucleation of right kidney. No other treatment was conducted after surgery. Outcomes: No metastases to lymph nodes and other organs were found, and 9-months of follow-up did not reveal any tumor progression. Lessons: We should differentially diagnose the renal metastasis of thyroid follicular carcinoma or papillary carcinoma. Some related literatures reported that the tumour cells had significant heteromorphism, several of which metastasized to lymph nodes or distal organs. Its biological behavior need to be studied intensively by further expanding the number of cases.